2018
DOI: 10.1111/papt.12169
|View full text |Cite
|
Sign up to set email alerts
|

Individual psychological therapy in an acute inpatient setting: Service user and psychologist perspectives

Abstract: Developing 'human' relationships at all levels of acute inpatient care continues to be an important challenge for clinical practice. Due to the distress of individuals and the constraints of the acute inpatient environment, psychologists need to be flexible and adaptable in delivering individual therapy. Making meaning and psychological formulation can give service users a sense of hope and empowerment, and can contribute to a shared understanding within the ward team of service users' difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 31 publications
5
55
0
Order By: Relevance
“…The delivery of psychological therapies was of equal priority to developing the therapeutic relationship; hence, a more informal approach to an initial assessment was required. This is in line with the previous research which identified the importance of inpatient psychological therapy being delivered within the context of a human relationship (Small et al, 2018). All adaptations to therapy reflected the need for psychological work to be responsive, delivered in a time-limited manner, and delivered to a population with complex needs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The delivery of psychological therapies was of equal priority to developing the therapeutic relationship; hence, a more informal approach to an initial assessment was required. This is in line with the previous research which identified the importance of inpatient psychological therapy being delivered within the context of a human relationship (Small et al, 2018). All adaptations to therapy reflected the need for psychological work to be responsive, delivered in a time-limited manner, and delivered to a population with complex needs.…”
Section: Discussionsupporting
confidence: 92%
“…To the author’s knowledge, only one relevant qualitative study has been conducted to examine psychologist’s experiences of psychological therapies in the acute psychiatric inpatient setting (Small, Pistrang, Huddy, & Williams, 2018). The authors identified that key components of inpatient psychological interventions were psychological formulation and the promotion of a therapeutic relationship.…”
Section: Introductionmentioning
confidence: 99%
“…These include the restrictive physical environment and treatment options, a service delivery system which is avoidant of emotions and feelings (Bentley, ), and working within a team which adopts a predominantly medical approach (Baguley, Alexander, Middleton, & Hope, ). It has been acknowledged the psychological therapies within the acute inpatient environment cannot be delivered in isolation (Small, Pistrang, Huddy, & Williams, ), and the support or involvement of the multidisciplinary team is crucial (Kerfoot, Bamford, & Jones, ).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the survey and interviews were analysed using Braun and Clarke's inductive reflexive thematic analysis (TA) [34]. This transparent technique has been previously used for similar studies because it is a systematic and rigorous approach to organising, describing, and interpreting data [35][36][37][38]. Braun & Clarke's approach to TA was selected because it is theoretically flexible but still gives a step-by-step process for conducting a thorough and transparent analysis.…”
Section: Discussionmentioning
confidence: 99%